Long Range Communication Radio Channel Propagation: A Review - Ruliyanta, Ruliyanta; Kusuma, Idris (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2025)
LoRa, or Long Range, is an increasingly popular wireless communication technology for Internet of Things (IoT) applications, offering long-distance connectivity with low power consumption. Radio channel propagation plays a critical role in determining the performance of a LoRa system. This paper provides a comprehensive review of radio channel propagation in the context of LoRa communications. It introduces various factors influencing LoRa signal propagation and examines recent research efforts aimed at understanding the propagation characteristics of LoRa radio channels and addressing the associated challenges. In conclusion, selecting an appropriate propagation model for LoRa, the propagation model requires consideration of environmental variations ranging from urban to rural settings. The Free Space Path Loss model is suitable for open areas and short distances, while the Log-Distance Path Loss provides flexibility across various conditions. The Okumura-Hata model is well-suited for urban and suburban environments, the ITU-R P.1546 model offers broad coverage across a wide range of environmental types, and the SUI model presents a comprehensive solution to a wide range of conditions. The appropriate model selection depends on the deployment of location, frequency of operation, and specific environmental conditions in which LoRa is implemented.